1954
DOI: 10.1002/hlca.19540370418
|View full text |Cite
|
Sign up to set email alerts
|

Kinetik der Decarboxylierung von p‐Aminosalicylsäure

Abstract: 3, 652 (1948).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

1956
1956
1971
1971

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…[9] would become equivalent to eq. [5] which does not fit the data. Equation [lo] also requires an isotope effect since k* cannot be eliminated from the equation in this pH range.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…[9] would become equivalent to eq. [5] which does not fit the data. Equation [lo] also requires an isotope effect since k* cannot be eliminated from the equation in this pH range.…”
mentioning
confidence: 88%
“…Willi and Stocker (5) found that the rate reaches a inaximum a t the isoelectric point and concluded that the rate-controlling step involves the protonation of 9-aminosalicylate anion, A-, a t the 1-position of the aroinatic ring. I-Iolvever, they found that, although the rate decreases as the pH is decreased below the isoelectric point, it does not decrease as fast as does the calculated value of [H+][A-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…59.1 mc./mmole)l, phosphorylribose-1-pyrophosphate2, nicotinamide monon~cleotide~, salicylic 1 Amersham Searle. 2 Mann Research Lab. …”
Section: Methodsmentioning
confidence: 99%
“…Decarboxylation of p-aminosalicylic acid into maminophenol and carbon dioxide was extensively studied (1)(2)(3)(4). It seems generally agreed that m-aminophenol did not have a significant role in the adverse reactions of p-aminosalicylic acid but that the chromogenic factors probably did'.…”
mentioning
confidence: 99%